The Genetic Architecture of Early Body Temperature and Its Correlation With Salmonella Pullorum Resistance in Three Chicken Breeds - Li, Xinghua; Nie, Changsheng; Liu, Yuchen; Chen, Yu; Lv, Xueze; Wang, Liang; Zhang, Jianwei; Yang, Weifang; Li, Kaiyang; Zheng, Chuanwei; Jia, Yaxiong; Ning, Zhonghua; et al. (Frontiers in Genetics, 2020)
New-born chicks are vulnerable to bacterial infections and not good at regulating body temperature. There is a close relationship between thermal regulation and immunity, however, the underlying mechanism is not well understood. Salmonella Pullorum (SP) is a major concern in developing countries and causes significant economic losses in poultry industry. Early body temperature (EBT) has previously shown to be correlated with host immunity and resistance to pullorum disease. In this study, we challenged three independent chick populations (Beijing You, Dwarf and Rhode Island Red) with SP at 4 days of age, and rectal temperature was measured before and after the SP attack from 2 to 7 days of age. Host defense to SP was evaluated by survival and spleen SP carrier status. The results showed that chicks with higher EBT before SP infection tend to have higher resistance to later SP attack in two populations (Dwarf and Beijing You). The association between EBT before SP attack and SP resistance was non-significant in Rohde Island Red population (P=0.06), but the trend was consistent with the other two populations. We also found low to moderate heritability in all three populations for EBT before and after the SP attack ranging from 0.14 ~ 0.20. Genome-wide association studies identified several genomic regions and biological pathways determining EBT before SP attack, which provides candidate functional genes of this trait. Our results reveal the genetic determination of EBT, and the relationship between EBT and SP resistance, providing an alternative strategy for improving SP resistant activities in chicken.